POLYPHENOLS IN YERBA MATE SEEDS: POTENTIAL INHIBITORS OF GERMINATION - Negra, Elisa Serra; Mireski, Maria Cecília; Bührer, Caroline de Bastos; Wendling, Ivar; dos Santos, Álvaro Figueredo; Helm, Cristiane Vieira; Nogueira, Antonio Carlos (Floresta, 2018)
Due to its economic, social, and ecological potentials, yerba mate can be a source of employment and income in the southern region of Brazil. The objectives of the present study was to (1) quantify the total polyphenols in fresh yerba mate seeds (FS), seeds dehydrated for 70 d (SD), and seeds stratified in sand for 180 d (SS); (2) evaluate the potential germination and growth inhibitory effects of water, ethanol + water (1:1), and ethanol (99%) extracts of yerba seeds (FS, SD, and SS) using lettuce seedlings; and (3) verify the presence of polyphenols in fresh seeds of yerba mate through histochemical methods. In the bioassay, extracts of yerba mate seeds were used in the germination of lettuce seeds. For the histochemical analysis, sections of yerba mate seeds were stained with specific dyes. The results revealed that yerba mate fresh seeds contain higher concentration of phenolic compounds, which decreased in dehydrated seeds, and almost no phenolic compound was observed in stratified seeds. The bioassay results showed that the polyphenols present in the extracts of yerba mate seeds resulted in phytotoxic effect on the roots of lettuce seedlings. The histochemical observations revealed the presence of “lignified rough barrier” and phenolic compounds between the endocarp and endosperm of the yerba mate seeds